Sebuah Studi Fenomenologi: Menelisik Informasi Akuntansi Usaha Kecil di Kota Palangka Raya - Wukuf Dilvan Rafa; Putri Balqis Fahrianti Octaviony; Shelly Laravida (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
Large companies are synonymous with their accounting implementation. This gives rise to the perception that only large companies can apply accounting, so small businesses are deemed not to need to apply accounting because of the low level of materiality, even though accounting is a business instrument. This research aims to examine accounting information, especially for small businesses, namely street vendors. This research is a type of qualitative research with a phenomenology data analysis approach. Data collection was carried out by conducting observations and in-depth interviews with the application of data reduction consisting of noema, noesis, bracketing, and eideric reduction. The research results stated that there was a separate understanding regarding the meaning of accounting; this happened because the informants had different levels of education. The first informant said that accounting is the basics of finance, buying and selling activities, and credit debits. The second informant defines accounting as expenditure and income activities until a final balance is obtained. The third, fourth, and fifth informants did not even know exactly what accounting was and only thought that accounting was for people who worked in a bank. The conclusion from this research is that all street vendors cannot understand the meaning of accounting and are unable to make business financial reports. The limitations of the research are related to the limited number of respondents, so it cannot be a basis for saying that all street vendors in Palangka Raya City do not understand accounting. Suggestions that can be given are to provide training for street vendors regarding financial reporting and the importance of making financial reports for businesses to provide opportunities for street vendors to obtain various funding and for future researchers to be able to review it from a quantitative aspect so that the amount of data obtained is more complete.